Reliability analysis on protection devices inclusion in LV residential distribution network - Mohd Ikhwan, Muhammad Ridzuan; Hernando-Gil, Ignacio; Djokić, Saša Ž (UTeM, 2018)
The inclusion and arrangement of protection devices within the LV distribution network often neglected. By exemption of protection devices during network modelling, may result in overestimation of reliability performances. Detail network representation of UK LV residential model is used to assess network reliability performance. The analytical and improved Monte-Carlo Simulation (MCS) approaches are used to estimate system-related reliability indices.